2020
DOI: 10.1002/adfm.201910738
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Flexible Hybrid Battery–Supercapacitor Based on a Self‐Assembled Vanadium‐Graphene Hydrogel

Abstract: A novel flexible hybrid battery–supercapacitor device is proposed consisting of high specific surface area electrodes paired with an electrolyte, which contains a redox species that can exist in more than two oxidation states. The two initially equal half‐cells of the device consist of a reduced graphene oxide hydrogel which encapsulates vanadium ions, synthesized with a single‐step method. During charge, the oxidation state of the vanadium ions changes, resulting in two half‐cells with different potentials wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Among all types of vanadium oxides, V 2 O 5 has been studied the most for energy storage applications; [10][11][12][13][14][15] however, there are benefits to employing mixed-valence vanadium oxides (VO x ), since VO 2 and V 2 O 3 have higher electrical conductivities than V 2 O 5 [16] and the pre-existing multiple oxidation states are likely to provide a larger electrochemical active potential window. [17,18] For example, Yu et al reported a valence optimized VO x electro-oxidized from V 2 O 3 that increased its potential window from 0.5 V for pure V 2 O 3 to 0.8 V after their electro-oxidized modification. [19] Supercapacitors have emerged as one of the leading energy-storage technologies due to their short charge/discharge time and exceptional cycling stability; however, the state-of-the-art energy density is relatively low.…”
Section: Doi: 101002/aenm202100768mentioning
confidence: 99%
“…Among all types of vanadium oxides, V 2 O 5 has been studied the most for energy storage applications; [10][11][12][13][14][15] however, there are benefits to employing mixed-valence vanadium oxides (VO x ), since VO 2 and V 2 O 3 have higher electrical conductivities than V 2 O 5 [16] and the pre-existing multiple oxidation states are likely to provide a larger electrochemical active potential window. [17,18] For example, Yu et al reported a valence optimized VO x electro-oxidized from V 2 O 3 that increased its potential window from 0.5 V for pure V 2 O 3 to 0.8 V after their electro-oxidized modification. [19] Supercapacitors have emerged as one of the leading energy-storage technologies due to their short charge/discharge time and exceptional cycling stability; however, the state-of-the-art energy density is relatively low.…”
Section: Doi: 101002/aenm202100768mentioning
confidence: 99%
“…Firstly, the force between the sheets is not uniform, so that some are strong and some are weak, resulting in the low overall strength of the material. Besides, the structural defect and disordered stack of the GHs lead to a poor electrical conductivity [134]. GAs not only have the advantages of graphene's high specific surface area and great conductivity, but also aerogel's characteristics of low density and high porosity [44].…”
Section: Problems Of Graphene Gels Used In Flexible Electrodesmentioning
confidence: 99%
“…As shown in Figure 13, 60 red light-emitting diodes (LED, 2.2 V) could be easily lit after charging for only 10 s in a single device filled only with ionic liquid electrolyte. The addition of transition metal oxide greatly improves the energy density of GHs [134]. Wang et al [139] prepared NiOOH nanosheets/GHs by solvothermal and hydrothermal mixing reactions.…”
Section: Ghs Flexible Supercapacitorsmentioning
confidence: 99%
“…However, the incorporation of pseudocapacitive materials would decelerate the charging and discharging rates, and diminish the stability of the devices. In addition, although graphene sheets are promising carbon materials for supercapacitors because of their high specific surface area, superior conductivity, and stable lattice structure, [39][40][41][42] their ease of stacking hinders the transport of ions and the infiltration of electrolytes into the electrode materials.…”
Section: Introductionmentioning
confidence: 99%